Development of a simple, rapid, and sensitive molecular diagnostic assay for cholera. - Subhra Chakraborty; Mirza Velagic; Sean Connor (Public Library of Science (PLoS), 2023)
Cholera continues to inflict high rates of morbidity and mortality. Prompt identification of cholera cases facilitates rapid outbreak responses in the short term while providing reliable surveillance data to guide long-term policies and interventions. Microbiological stool culture, the current recognized gold standard for diagnosing cholera, has significant limitations. Rapid diagnostic tests (RDTs) represent promising alternatives for diagnosing cholera in areas with limited laboratory infrastructure. However, studies conducted with the current cholera RDTs demonstrated wide variations in sensitivity and specificity. To address this gap in the diagnosis of cholera, we developed a simple, rapid, and sensitive diagnostic assay, "Rapid LAMP based Diagnostic Test (RLDT)." With a novel, simple sample preparation method directly from the fecal samples along with lyophilized reaction strips and using established Loop-mediated Isothermal Amplification (LAMP) platform, cholera toxin gene (ctxA) and O1 (O1rfb) gene could be detected in less than an hour. Cholera RLDT assay is cold chain and electricity-free. To avoid any end-user bias, a battery-operated, handheld reader was used to read the RLDT results. The performance specifications of the cholera RLDT assay, including analytical sensitivity and specificity, were evaluated using direct fecal samples, dried fecal samples on filter paper, and environmental water samples spiked with cholera strain. The limit of detection (LOD) was ~104 CFU/gm of stool for both ctxA and O1 genes, corresponding to about 1 CFU of Vibrio cholerae per reaction within 40 minutes. The LOD was 10 bacteria per ml of environmental water when tested with RLDT directly, without enrichment. Being simple, RLDT has the potential to be applied in resource-poor endemic settings for rapid, sensitive, and reliable diagnosis of cholera.